A PROGRAM TO DEAL WITH VOLUNTARY SMOKING RESTRICTIONS IN THE WORKPLACE (Tufts Archival Research Center, 2007)
Report outlining a program authored by the Tobacco Institute to better explain the implications of smoking restrictions to policy makers. States program objectives, including discouraging policy makers from unfairly discriminating against employees who smoke and increasing public understanding of smoking restrictions as often unfair and unnecessary. Explains the organization of the program, focusing on five task forces and also mentioning a coordinating committee, full-time professional staff member and consultants.